ORGANIZING AND CONDUCTING NATIONAL MOVEMENT GAMES IN PHYSICAL EDUCATION CLASSES - Moydinov Iqboljon Abduxamidovich; Abduxamidov Asadbek Iqboljon ogli (The Conference Hub, 2025)
This research explores the importance of national movement-based games in physical education classes and examines effective methods for organizing and conducting such games. National games not only enhance students’ physical activity but also play a vital role in bringing them closer to national culture, traditions, and values. The paper analyzes how to effectively incorporate these games into physical education lessons, outlines their pedagogical goals, and discusses their influence on the educational process.
Keywords: Physical education, national games, movement games, organization, implementation, sports, traditions, educational process, teamwork, healthy lifestyle, competition, game rules, physical development.